COX-2 Inhibition by Diclofenac Is Associated With Decreased Apoptosis and Lesion Area After Experimental Focal Penetrating Traumatic Brain Injury in Rats - Dehlaghi Jadid, Kayvan; Davidsson, Johan; Lidin, Erik; Hånell, Anders; Angéria, Maria; Mathiesen, Tiit; Risling, Mårten; Günther, Mattias (Frontiers in Neurology, 2019)
Traumatic brain injury (TBI) is followed by a secondary inflammation in the brain. The inflammatory response includes prostanoid synthesis by the inducible enzyme cyclooxygenase-2 (COX-2). Inhibition of COX-2 is associated with improved functional outcome in experimental TBI models, although central nervous system-specific effects are not fully understood. Animal studies report better outcomes in females than males. The exact mechanisms for this gender dichotomy remain unknown. In an initial study we reported increased COX-2 expression in male rats, compared to female, following experimental TBI. It is possible that COX-2 induction is directly associated with increased cell death after TBI. Therefore, we designed a sequential study to investigate the blocking of COX-2 specifically, using the established COX-2 inhibitor diclofenac. Male Sprague-Dawley rats weighing between 250 and 350 grams were exposed to focal penetrating TBI and randomly selected for diclofenac treatment (5 µg intralesionally, immediately following TBI) (n=8), controls (n=8), sham operation (n=8) and normal (no manipulation) (n=4). After 24h, brains were removed, fresh frozen, cut into 14 µm coronal sections and subjected to COX-2 immunofluorescence, Fluoro-Jade, TUNEL and lesion area analyses. Diclofenac treatment decreased TUNEL staining indicative of apoptosis with a mean change of 54% (p<0.05) and lesion area with a mean change of 55% (p<0.005). Neuronal degeneration measured by Fluoro-Jade and COX-2 protein expression levels were not affected. In conclusion, COX-2 inhibition by diclofenac was associated with decreased apoptosis and lesion area after focal penetrating TBI and may be of interest for further studies of clinical applications.